An investigation into low-inertia grid stability with high injection of variable renewable energy sources - Lewis, Jordana; Burmester, Daniel (Archives of Sustainable Energy Systems, 2025)
As the world moves towards decarbonising the energy sector, variable renewable energy sources (VRES) are seen as an integral part of the transition. Much has been researched about the different forms of VRES, which are also known as inverter-based resources (IBR), and of the challenges of integrating them into pre-existing grid infrastructure. Nevertheless, the complex dynamics and impacts on grid stability, particularly within low-inertia grids, are case-specific and so warrant continued attention. This research analyses the specific response of one such grid, on Rakiura Stewart Island of Aotearoa New Zealand, to increasing solar photovoltaic capacity. Issues such as generator motoring and voltage rise are encountered, which suggest that the grid would also see frequency rises. As the capacity of VRES penetration increases, the effects are enhanced. Comparing the results show that negative effects are overall better mitigated by using a decentralised approach, as this offers more even distribution of the generation burden, lower line voltage drops, decreased line losses, and greater line loading reductions. Decentralised systems also have the advantage when it comes to decreasing loading on diesel generators in the grid, reducing fuel use and lengthening the lifespan of the generators. In exchange for these benefits, however, decentralised installations introduce higher node voltages and increase coordination complexity for seamless operation. Subsequent investigations should focus on the strategic integration of energy storage and power electronics, including flexible alternating current transmission system (FACTS) devices and static synchronous compensators (STATCOMs).